Gastric carcinoid tumor resected with endoscopic polypectomy - Selim GÜREL; Enver DOLAR; Selim Giray NAK; Gülaydan FİLİZ and Macit GÜLTEN and Yusuf KARAASLAN and Ömer YERCİ and Faruk MEMİK (Turkish Journal of Gastroenterology, 2019)
-